2021
DOI: 10.24123/aipj.v36i2.2880
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Well-Being of Indonesian Children: A Perspective of Material Well-Being [Kesejahteraan Subjektif Anak Indonesia: Sebuah Perspektif Kesejahteraan Materi]

Abstract: This study aims to explain the subjective well-being of Indonesian children in terms of material well-being. Indonesia is still considered a developing country, and several studies reveal the correlation between economic status and subjective well-being of adults. However, only a very limited number of studies focus on Indonesian children’s material well-being from their own perspective. This study used data from the third wave of the Children’s Worlds survey conducted in Indonesia. The sample (N = 14,576; 49.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 36 publications
1
2
0
5
Order By: Relevance
“…Large-scale research on well-being from a material perspective of Indonesian children shows that 55% (N=7213) experience conditions of deprivation. Apart from that, the results of this research also show that children in lower-middle economic conditions have low subjective well-being ( Sabriani, 2020;Borualogo & Casas, 2022). Research conducted by Dearly (2022) on young children with middle socioeconomic status showed that only 10% of children had high levels of subjective well-being.…”
Section: Introductionsupporting
confidence: 56%
“…Large-scale research on well-being from a material perspective of Indonesian children shows that 55% (N=7213) experience conditions of deprivation. Apart from that, the results of this research also show that children in lower-middle economic conditions have low subjective well-being ( Sabriani, 2020;Borualogo & Casas, 2022). Research conducted by Dearly (2022) on young children with middle socioeconomic status showed that only 10% of children had high levels of subjective well-being.…”
Section: Introductionsupporting
confidence: 56%
“…Poliviktimisasi perundungan diukur menggunakan alat ukur frekuensi perundungan dari Children's Worlds yang mengukur frekuensi perundungan di sekolah oleh siswa lain dan perundungan di rumah oleh saudara kandung [8], lalu SWB diukur menggunakan Children's Worlds Subjective Well-Being Scale 5 (CW-SWBS5) [8], [15] dan Children's Worlds Positive and Negative Affect (CW-PNAS) [3], [15], untuk memberikan gambaran latar belakang ekonomi keluarga partisipan di ukur menggunakan status sosial ekonomi (SES) [3]. Semua alat ukur yang digunakan dalam penelitian ini sudah diadaptasi ke dalam bahasa dan konteks budaya indonesia.…”
Section: Bunclassified
“…Anak-anak yang melakukan latihan fisik setiap hari, melakukan aktivitas sehari-hari bersama keluarga, dan tidak pernah khawatir dengan uang menunjukan SWB yang lebih tinggi [11]. Dalam sebuah penelitian menunjukkan bahwa anak-anak yang berasal dari keuarga yang memiliki status ekonomi rendah dan tidak memiliki cukup makanan yang dapat dikonsumsi sehari-hari seringkali merasa khawatir mengenai keuangan keularganya, menunjukkan tingkat SWB yang rendah [12].…”
Section: Aunclassified